1995
DOI: 10.7326/0003-4819-123-2-199507150-00009
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine and 6-Mercaptopurine in Crohn Disease

Abstract: Azathioprine and 6-mercaptopurine are effective in treating active Crohn disease and in maintaining remission. Cumulative dose was an important factor in predicting response. Adverse effects were more common among patients receiving therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
524
3
30

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 911 publications
(568 citation statements)
references
References 0 publications
11
524
3
30
Order By: Relevance
“…In our series, the probability of remission with corticosteroid withdrawal after 6 and 12 months of remission in patients with active disease at the initiation of the drug was 46% and 79%, respectively, a rate similar to the one reported with AZA/MP. 1,[37][38][39] In patients on TG maintenance therapy, the probability of relapse at 6 and 12 months was 29% and 53%, respectively. The number of patients available for the evaluation of the TG maintenance effect is small (n ¼ 28), and the followup period is still short (median 5 months).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our series, the probability of remission with corticosteroid withdrawal after 6 and 12 months of remission in patients with active disease at the initiation of the drug was 46% and 79%, respectively, a rate similar to the one reported with AZA/MP. 1,[37][38][39] In patients on TG maintenance therapy, the probability of relapse at 6 and 12 months was 29% and 53%, respectively. The number of patients available for the evaluation of the TG maintenance effect is small (n ¼ 28), and the followup period is still short (median 5 months).…”
Section: Discussionmentioning
confidence: 99%
“…Among 21 of them, remission was achieved without corticosteroids or infliximab during the follow-up period (median duration 7 months, range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The probability of remission without corticosteroids or infliximab was 46% (95% CI, 37-55%) and 79% (95% CI, 70-88%) at 6 and 12 months, respectively ( Figure 2).…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis by Pearson et al [57] reported an odds ratio of 3.09 for response to therapy over placebo. In the more recent meta-analyses conducted for the Cochrane database, a pooled effi cacy of 54% and 71% for induction and maintenance of CD remission was reported for AZA [58,59].…”
Section: Thiopurinesmentioning
confidence: 99%
“…The immunosuppressants, azathioprine (AZA) and 6‐mercaptopurine (6‐MP), are used as a second‐line therapy in almost 60% of patients with IBD to induce and maintain remission 1, 2, 3, 4, 5, 6. The recommended dose of AZA is up to 2.5 mg/kg and that of 6‐MP is 1–1.5 mg/kg/day.…”
Section: Introductionmentioning
confidence: 99%